Tics and Tourette syndrome : a handbook for parents and professionals - Chowdhury, Uttom, 1967- (Jessica Kingsley, 2004)
This essential guide to tic disorders and Tourette Syndrome tackles problems faced both at home and at school, such as adjusting to the diagnosis, the effect on siblings and classroom difficulties. Dr Chowdhury offers advice on how to manage symptoms, describing psychological techniques such as habit reversal and massed practice and reviewing available medical treatments. In clear, accessible language, this book explains the clinical signs and symptoms of Tourette and related conditions, and their possible causes. Presenting practical strategies for dealing with associated difficulties, includ.